The American ideal : literary history as a worldly activity - Carafiol, Peter C. (Oxford University Press, 1991)
This monograph argues that the institution of American literary scholarship enshrines a reactionary view of history and narrative and an unrealistic view of America itself. The author also examines contemporary debates about the methods and status of literary history in general.